An engineering perspective of vacuum assisted delivery devices in obstetrics: A review. (January 2021) - Goordyal, Dushyant; Anderson, John; Alazmani, Ali; Culmer, Peter
Complications during childbirth result in the need for clinicians to use 'assisted delivery' in over 12% of cases (UK). After more than 50 years in clinical practice, vacuum assisted delivery (VAD) devices remain a mainstay in physically assisting child delivery; sometimes preferred over forceps due to their ease of use and reduced maternal morbidity. Despite their popularity and enduring track-record, VAD devices have shown little evidence of innovation or design change since their inception. In addition, evidence on the safety and functionality of VAD devices remains limited but does present opportunities for improvements to reduce adverse clinical outcomes. Consequently in this review we examine the literature and patent landscape surrounding VAD biomechanics, design evolution and performance from an engineering perspective, aiming to collate the limited but valuable information from a disparate field and provide a series of recommendations to inform future research into improved, safer, VAD systems.